Processing of ferrous iron and steel waste in the context of the circular economy. Issue 1 (February 2021) - Lupu, O; Socalici, A; Popa, E; Gaianu, O
Abstract: The paper presents the possibilities of exploiting the small and powdered ferrous waste with the production of lighters that can be used as a raw material in the loading of the steel processing units. The capitalization of small ferrous and powdered iron and steel wastes is an important problem, because their transformation into by-products, so in economic goods can lead to a rational exploitation of the resources of raw materials and energy, thus ensuring both the needs of the human society and the protection of the environment surrounding.